The Discursive Dynamics in Teacher Education: Authoritative Discourse or Internally Persuasive Discourse? - Maria Otilia Guimarães Ninin; Ângela Brambilla Cavenaghi Themudo Lessa (Bakhtiniana: Revista de Estudos do Discurso, 2014)
This article, based on the socio-cultural-historical theoretical perspective, discusses the activity in which individuals engage as constitutive of the social roles they occupy. It aims to trigger discussion of discursive dynamics in the context of critical-collaborative teacher education, focusing on internally persuasive and authoritative discourse (BAKHTIN, 1981) and their co-occurrence in situations of negotiation of meanings. This distinction is relevant because it is possible to understand different argumentative enunciations or not, conducted by educators in training, which approach or distance themselves from those cast by their trainers or isolated voices of theoretical practice, indicating possibilities of creation or reduction of dialogic expansion. From the emphasis on internally persuasive discourse, this article highlights the critical - collaborative argumentation role in training educators. Examples selected from a corpus of research collected in public school in São Paulo subsidize the discussion supported by Bakhtin (1981) and Vygotsky (1998; 2001).